Exploring the role of Dynamic Presencing in a group coaching training context for fostering transformative leadership development in disruptive times - Proches, Cecile Gerwel; Daya, Preeya; Strayer, Jessica; Leask, Cristy; Mngadi, Ntokozo; de Lange, Christa; Gunnlaugson, Olen (Frontiers in Psychology, 2024)
With the growing array of challenges that humanity is experiencing since the global pandemic, knowledge workers at all levels of organizations are experiencing a noted increase in the volatility, uncertainty, complexity and ambiguity (VUCA) conditions of our work and lives. This has brought about significant changes in ways of working and associated ways of being that have become more fragmented and virtual. Disruptive change continues to unfold on many levels of society from the organizational to the individual, with multiple and often unintended consequences. This article outlines how the body of work of Dynamic Presencing in a group coaching context facilitates responsive forms of personal development as well as a deeper transformation of one's leadership identity in the face of such change, in turn serving as an approach that can be useful in navigating VUCA conditions that are becoming increasingly prevalent. The transformative process of Dynamic Presencing develops core inner leadership capabilities with a noted increase in the quality of internal as well as interpersonal forms of selfpresence-and presencing-awareness. Overall, Dynamic Presencing serves as a critical enabler of presencing mastery, which instils a deeper confidence and resourcefulness in working with the VUCA conditions of our global world by deepening our presencing process and refining our methods for inner leadership development in turbulent times.